Asset-Based Reserve Requirements: A New Monetary Policy Instrument for Targeting Diverging Real Estate Prices in the Euro Area - Michael Holz (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2007)
Can monetary policy prevent real estate bubbles from harming economic welfare? The European Central Bank (ECB) has to conduct monetary policy for the Euro area as a whole, but her policy affects countries with rapidly rising house prices (e.g. Spain) in a markedly different way than those with stagnating house prices (like Germany). For opposing divergent real estate price developments within the European Monetary Union (EMU), interest rate policy is not the appropriate instrument; whereas "fine tuning" may be possible with the help of asset-based reserve requirements. All financial institutions would be forced to deposit them at the ECB (as a percentage of asset holdings). Reserve rates are free to vary between countries. Therefore, rates should be highest in those countries where appropriate indicators signal a house price bubble.
Keywords: E44; E52; G18; 330; monetary policy; real estate prices; Tobin's Q; minimum reserve policy; financial stability